Processed grain sorghum and grain sorghum combinations for dairy cows - Evan C. Titgemeyer; James S. Drouillard; A.F. Park; John E. Shirley (Kansas Agricultural Experiment Station Research Reports, 1998)
Twenty-four Holstein cows were used to evaluate the effects of processing methods on grain sorghum utilization by lactating dairy cows. No difference was observed in the utilization of steam-flaked grain sorghum and pelleted grain sorghum obtained by adding water to finely ground grain sorghum prior to extrusion and oven drying at a temperature of 200EF. Extensive processing (pelleting or steam-flaking) improved feed efficiency relative to dry rolling. Cows fed diets containing more extensively processed grains ate less feed but produced the same amount of milk as cows fed diets containing dry-rolled grain.; Dairy Day, 1998, Kansas State University, Manhattan, KS, 1998;
Keywords: Dairy Day; 1998; Kansas Agricultural Experiment Station contribution; no. 99-158-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 821; Lactating cows; Processed grain sorghum; Dry-rolled grain sorghum